P135. EEG-based assessment of wakefulness regulation in different mood states in bipolar disorder – A retrospective analysis. Issue 8 (August 2015) - Wittekind, D.A.; Sander, C.; Spada, J.; Groß, A.; Hegerl, U.
<x xml:space="preserve">Abstract</x> Background According to the vigilance theory of affective disorders, unipolar depression is characterised by a hyperstable wakefulness regulation, meaning that patients suffering from depression show a high alertness and a less distinct and later decline into lower vigilance and sleep states. Mania on the other hand is associated with an unstable wakefulness regulation with a rapid decline into sleep states and quickly alternating wakefulness states (Hegerl and Hensch, 2012). This theory has been backed up for unipolar depression in recent years (Hegerl et al., 2012). However, so far EEG-based assessment of wakefulness regulation has not been performed for bipolar patients in different mood states. Objective The aim of this study is to assess and to compare wakefulness regulation in bipolar depression, mania and euthymia. This will be done both for diagnostic groups as well as for individual patients for whom EEG-recordings in all mood states are available. Methods This is going to be a retrospective, cross-sectional analysis. In the department of psychiatry at the university hospital in Leipzig, inpatients suffering from bipolar mania/depression and bipolar outpatients in euthymia undergo a 15-min resting EEG. Strict inclusion and exclusion criteria were defined to ensure comparability of results. So far, we have included 23 manic, 13 hypomanic and 51 depressive patients suffering from bipolar disorder. Mood at the time of EEG-recording is assessed via the Young Mania Rating Scale (YMRS) and the 17-item Hamilton rating scale for depression (HAMD-17). EEG-vigilance regulation will be determined with a computer-based vigilance classification algorithm (VIGALL, Vigilance Algorithm Leipzig), allowing a classification of vigilance stages A (with substages A1, A2 and A3), B (with substages B1 and B2/3) and C. Hypothesis We hypothesize that currently depressive bipolar patients will show hyperstable wakefulness, while currently manic patients will show an unstable wakefulness regulation. Furthermore, we hypothesize that this is a state – rather than a trait – dependent regulation.